Are prophylactic antibiotics beneficial for preventing cellulitis in patients with a history of recurrent cellulitis?. Issue 1 (January 2016) - Mahowald, Megan; Sloan, Dawn
Abstract : Evidence‐Based Answer : Prophylactic antibiotics decrease the risk of recurrence by 45% to 54% in patients with a history of recurrent cellulitis; however, the ideal antibiotic, method of administration, and duration of treatment are unclear (SOR: A, systematic review with meta‐analysis). Once prophylactic antibiotics are stopped, the rate of recurrence rises again to baseline (SOR: B, RCT).